Type VII Collagen Expression in the Human Vitreoretinal Interface, Corpora Amylacea and Inner Retinal Layers. - Bart Wullink; Hendri H Pas; Roelofje J Van der Worp; Roel Kuijer; Leonoor I Los (PLoS ONE)
Type VII collagen, as a major component of anchoring fibrils found at basement membrane zones, is crucial in anchoring epithelial tissue layers to their underlying stroma. Recently, type VII collagen was discovered in the inner human retina by means of immunohistochemistry, while proteomic investigations demonstrated type VII collagen at the vitreoretinal interface of chicken. Because of its potential anchoring function at the vitreoretinal interface, we further assessed the presence of type VII collagen at this site. We evaluated the vitreoretinal interface of human donor eyes by means of immunohistochemistry, confocal microscopy, immunoelectron microscopy, and Western blotting. Firstly, type VII collagen was detected alongside vitreous fibers6 at the vitreoretinal interface. Because of its known anchoring function, it is likely that type VII collagen is involved in vitreoretinal attachment. Secondly, type VII collagen was found within cytoplasmic vesicles of inner retinal cells. These cells resided most frequently in the ganglion cell layer and inner plexiform layer. Thirdly, type VII collagen was found in astrocytic cytoplasmic inclusions, known as corpora amylacea. The intraretinal presence of type VII collagen was confirmed by Western blotting of homogenized retinal preparations. These data add to the understanding of vitreoretinal attachment, which is important for a better comprehension of common vitreoretinal attachment pathologies.